Globalization and Imperfect Labor Market Sorting - Carl Davidson; Fredrik Heyman; Steven Matusz; Fredrik Sjöholm; Susan Chun Zhu (Research Institute of Industrial Economics (IFN), 2010)
This paper focuses on the ability of the labor market to correctly match heterogeneous workers to jobs within a given industry and the role that globalization plays in that process. Using matched worker-firm data from Sweden, we find strong evidence that openness improves the matching between workers and firms in export-oriented industries. This suggests that there may be significant gains from globalization that have not been identified in the past globalization may improve the efficiency of the matching process in the labor market. On the other hand, we find no evidence that openness affects the degree of matching in import-competing industries. These results remain unchanged after adding controls for technical change at the industry level or measures of domestic anti-competitive regulations and product market competition. In addition, we find no evidence that technical change has any impact on the degree of matching at the industry level. Our results are also robust to alternative measures of the degree of matching, openness, or the trade status of an industry.
Keywords: F14; F16; J20; 330; Matching; Firms; Workers; Globalization; Sweden; Arbeitsplatzsuchmodell; Multinationales Unternehmen; Globalisierung; Qualifikation; Technischer Fortschritt; Schweden